(untitled) (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
Abstract. In this work a macroscopic viscoplastic model, accounting for strain, strain rate hardening and instantaneous rate sensitivity of FCC metals, is formulated. Within the present approach, a single phenomenological internal variable representing an effective microstructural feature is introduced. In a phenomenological way, this internal variable is related to hardening mechanisms associated with large strain processes. Aiming at applying the constitutive proposal in solving engineering problems, associated numerical formulation is also described. Reasoning on the numerical context, an exponential implicit integration scheme is adopted together with an elastic predictor-plastic corrector algorithm. Constitutive capabilities are assessed by solving simple numerical problems involving high-strain-rate deformation. Simulation results and comparisons with experimental data available in the literature, considering an annealed high purity copper, demonstrate the model aptitude in predicting strain rate history effects on material response. In general, proposed model proves to be a useful modeling alternative to describe the macroscopic behavior of FCC metals subjected to high-strain-rate cold deformation. Keywords: High strain rate effects, Finite strains, Viscoplasticity, Numerical algorithms